Relationship between Birth Weight and Speech Delay in Children - Ulfatul Latifah; Riska Arsita; Iroma Maulida (GLOBAL HEALTH SCIENCE GROUP, 2025)
Speech Delay is a condition where the quality of children's speech development is not appropriate or is below their age, children have difficulty expressing their feelings and lack of vocabulary mastery in children. According to the Indonesian Ministry of Health, it is explained that the toddler period is an important period in the growth and development of the next child, speech and language delays (Speech Delay) in Indonesia as much as 5%-10% in preschool children. Speech Delay is estimated to occur by several factors, namely intelligence, language use, speech style/model imitated, family relationships, health, genetics, physical disability, neurological malfunctions, gender, maternal education, socioeconomic status, family function, and number of children. This study aims to determine the effect and risk of speech delay in children with a history of being born with normal weight and those born with abnormal weight. By knowing the risk factors for speech delay in children, it is hoped that prevention efforts can be made so as to reduce the incidence of speech delay in children in the community. This type of research is analytic observational using a cross-sectional design, with a quantitative approach. The population in this study were parents who had children aged 2-5 years. The sample in this study were parents who had children aged 2-5 years experiencing speech delay disorders and who did not experience speech disorders as controls. Selection of research subjects using purposive sampling. The analysis test used was chis square test. Quantitative research data collection was carried out by filling out questionnaires through questionnaires and google form. Research results shows there is a relationship between birth weight and the incidence of speech delay (p value=0.045). The results of the OR calculation show that respondents who have a history of birth weight <2500 grams and > 4000 grams are at risk of 2.286 experiencing speech delay in children compared to respondents who have a history of birth weight 2500gram - 4000gram.